Efficacy of Metformin and Combination of Metformin and Myo-Inositol on Clinical and Hormonal Profile of Polycystic Ovarian Disease Patient - Rehman , Mounazza; Nawaz, Qudsia; Batool , Siddiqa; Khanum , Faiza; Raja , Sehrish; Andleeb , Munnaza (Indus Journal of Bioscience Research, 2025)
Background: The widespread endocrine condition known as polycystic ovarian syndrome (PCOS) is typified by hyperandrogenism, insulin resistance, and reproductive failure. Metformin, a commonly used insulin sensitizer, has showed benefits in controlling PCOS but is often linked with gastrointestinal adverse effects. Another insulin-sensitizing drug that has drawn interest is myo-inositol because of its superior tolerability and comparable effectiveness. The purpose of this study is to compare the clinical and hormonal effects of metformin monotherapy against myo-inositol combination treatment in patients with PCOS. Methods: At a Combined Military Hospital CMH, Lahore, 150 women with PCOS diagnoses based on the Rotterdam criteria were enrolled. Subjects were randomized to either the combination therapy group (metformin + myo-inositol, n = 75) or the metformin monotherapy group (n = 75). Pregnancy outcomes, ovulation rates, hormonal profiles, metabolic indicators, and clinical parameters were evaluated both before and after treatment. Additionally, adverse consequences were noted. Results: Combination therapy produced better results in raising SHBG levels and decreasing BMI, fasting insulin, HOMA-IR, and total testosterone levels. The combination group saw higher rates of ovulation (78% vs. 65%), menstrual regularity (85% vs. 72%), and pregnancy (30% vs. 22%) than the metformin monotherapy group. The combined medication group saw considerably less gastrointestinal side effects, which improved patient adherence. Conclusion: In PCOS patients, metformin and myo-inositol work better together to improve metabolic, hormonal, and reproductive results while lowering side effects. According to these results, combined medication might be a better and more palatable option for treating PCOS than metformin by itself.